The role of perfluorooctane sulfonic acid (PFOS) exposure in inflammation of intestinal tissues and intestinal carcinogenesis - Durham, Jerika; Tessmann, Josiane Weber; Deng, Pan; Hennig, Bernhard; Zaytseva, Yekaterina Y. (Frontiers in Toxicology, 2023)
PFAS (per- and polyfluoroalkyl substances) are organofluorine substances that are used commercially in products like non-stick cookware, food packaging, personal care products, fire-fighting foam, etc. These chemicals have several different subtypes made of varying numbers of carbon and fluorine atoms. PFAS substances that have longer carbon chains, such as PFOS (perfluorooctane sulfonic acid), can potentially pose a significant public health risk due to their ability to bioaccumulate and persist for long periods of time in the body and the environment. The National Academies Report suggests there is some evidence of PFOS exposure and gastrointestinal (GI) inflammation contributing to ulcerative colitis. Inflammatory bowel diseases such as ulcerative colitis are precursors to colorectal cancer. However, evidence about the association between PFOS and colorectal cancer is limited and has shown contradictory findings. This review provides an overview of population and preclinical studies on PFOS exposure and GI inflammation, metabolism, immune responses, and carcinogenesis. It also highlights some mitigation approaches to reduce the harmful effects of PFOS on GI tract and discusses the dietary strategies, such as an increase in soluble fiber intake, to reduce PFOS-induced alterations in cellular lipid metabolism. More importantly, this review demonstrates the urgent need to better understand the relationship between PFOS and GI pathology and carcinogenesis, which will enable development of better approaches for interventions in populations exposed to high levels of PFAS, and in particular to PFOS.